The Consequences of the Pandemic: Pro-Social Practices and Community Solidarity - Oksana A. Polyushkevich (Гуманитарный вектор)
The relevance of the work is in studying the impact of pro-social practices on the social solidarity of society after the COVID-19 pandemic. The purpose of the study was pro-social practices and processes of social solidarity in a pandemic. The research methods were electronic diaries of participants in pro-social practices and their publications on social networks about which events they took part in. As a result of the study, we found that a decrease in habitual activity led to a desire to seek additional activity, its main motives are four key meanings of prosocial activity (care for others, participation in socially useful activities, the opportunity to share one’s experience and knowledge, form social capital, be useful and needed by other people). Among pro-socially active people, a high level of trust in the government has been established, which was formed during the pandemic and continues to this day as an internal confidence in the correctness of decisions made at any level, while fear as a social phenomenon that took shape during the start of the pandemic now continues, but is transforming into new levels and forms of anxiety. The key role of negative emotional experiences and emotional stress is emphasized, the counterbalance (struggle) against which was participation in prosocial practices, emphasis is placed on strengthening the best and worst qualities of a person in a pandemic and participation in prosocial activities, this either enhances positive or smooths out negative qualities. It is also concluded that education and health are more important than consumption, this determines the format of new meaningful life guidelines for participants in pro-social practices. The novelty of this study lies in the conclusion that the consequence of the new living conditions after the pandemic are alternative behaviors, new meanings of life and life scenarios. The prospect of further research is to monitor the more distant consequences of the COVID-19 pandemic, their impact on social identity and community solidarity.